Anisotropic Magnetism in Gradient Porous Carbon Composite Aerogels - Bahner, Jochen; Hug, Nicolas; Polarz, Sebastian (My University, 2021)
Porosity is of high importance for functional materials, as it allows for high surface areas and the accessibility of materials. While the fundamental interplay between different pore sizes and functionalities is quite well understood, few studies on gradually changing properties in a material exist. To date, only a few examples of such materials have been synthesized successfully. Herein, we present a facile method for synthesizing macroscopic carbon aerogels with locally changing pore sizes and functionalities. We used ultracentrifugation to fractionate differently functionalized and sized polystyrene nanoparticles. The assembly into gradient templates was conducted in a resorcinol–formaldehyde (RF) sol, which acted as a liquid phase and carbon precursor. We show that the modification of nanoparticles and a sol–gel precursor is a powerful tool for introducing dopants (sulfur and phosphorous) and metal nanoparticles (e.g., Ni) into gradient porous carbons formed during the carbonization of the RF sol. Understanding the underlying interactions between particles and precursors will lead to a plethora of possibilities in the material design of complex functionally graded materials. We showed this by exchanging parts of the template with magnetite–polystyrene composites as templating nanoparticles. This led to the incorporation of magnetite nanoparticles in the formed gradient porous carbon aerogels. Finally, gradually increasing concentrations of magnetite were obtained, ultimately leading to macroscopic carbon aerogels with locally changing magnetic properties, while the graded porosity was maintained.
Keywords: hierarchical porosity; aerogel; functional gradient material; graded porosity; composite materials; magnetism; carbon; magnetite; 540